Origins and perspectives of the humanitarian corridors' programme: Just a matter of economic sustainability? - Gianluca Gerli (The Journal of European Economic History (JEEH), 2024)
As the Humanitarian Corridors' programme is gaining more attention in the international debate, this article goes back to its onset through original documentation. An in-depth analysis of its first memoranda of understanding will help to shed light on how everything started and how a pilot project became one of the most viable solutions prompted by the EU to the so-called migration crises. After retracing the origins of this initiative through a historical approach, the present contribution offers finally a reflection about possible developments of Humanitarian Corridors in international politics, both at a European level and in a wider sense.
Keywords: 330; Humanitarian aid; Refugees; Migration policy; EU states; Humanitäre Hilfe; Flüchtlinge; Migrationspolitik; EU-Staaten